2005
DOI: 10.4049/jimmunol.174.3.1153
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids and the Balancing of Immune Cell Function: Lessons from the Mast Cell

Abstract: Recent studies reveal that metabolites of sphingomyelin are critically important for initiation and maintenance of diverse aspects of immune cell activation and function. The conversion of sphingomyelin to ceramide, sphingosine, or sphingosine-1-phosphate (S1P) provides interconvertible metabolites with distinct biological activities. Whereas ceramide and sphingosine function to induce apoptosis and to dampen mast cell responsiveness, S1P functions as a chemoattractant and can up-regulate some effector respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 58 publications
3
109
0
Order By: Relevance
“…Polymerase chain reaction (PCR) and microarray analysis of various sources of MC RNA for R4 RGS family members revealed expression of Rgs1, 8,13,16 13 and 18 (data not shown). We focused on Rgs13 because microarray studies of purified human cell subsets showed restricted RGS13 expression in MCs compared to other hematopoietic cells (Fig.…”
Section: Enrichment Of Rgs13 In Mcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerase chain reaction (PCR) and microarray analysis of various sources of MC RNA for R4 RGS family members revealed expression of Rgs1, 8,13,16 13 and 18 (data not shown). We focused on Rgs13 because microarray studies of purified human cell subsets showed restricted RGS13 expression in MCs compared to other hematopoietic cells (Fig.…”
Section: Enrichment Of Rgs13 In Mcsmentioning
confidence: 99%
“…RGS isoforms can be further divided into subfamilies on the basis of additional protein interaction motifs. However, the R4 subfamily of 8,13,16,18,and 21) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of immunosuppression by FTY720, however, is associated with such a broad spectrum of serious ocular, pulmonary and cardiac complications that alternative agents and approaches are being sought which have S1P 1 R selectivity, a greater ratio of antagonist and downregulator functions to agonist activity, and preferential organ system effects. One very hopeful therapeutic possibility is a recently discovered cluster of monoclonal anti-S1P 1 Abs that inhibit lymphocyte functional responses to S1P. Two clear advantages of these monoclonal antibodies are absolute specificity and the greater ability to focus effective inhibitory concentrations of a protein than a small organic compound at a tissue site of involvement of the S1P-S1P 1 axis.…”
Section: Levels Of Regulation Of S1p-s1p 1 Axis Effects On T Cell Tramentioning
confidence: 99%
“…Sphingosine 1-phosphate (S1P), that is produced principally by stimulated mast cells and mononuclear phagocytes in tissues and by erythrocytes in blood [1,2], is a major mediator of T cell lymphoid traffic, tissue migration, proliferation and cytokine secretion [3][4][5][6]. Of the family of G protein-coupled receptors (GPCRs) with high specificity for S1P, the type 1 receptor (S1P 1 ) predominates in its level of expression and transduction of diverse T cell functional responses [7,8].…”
Section: Introductionmentioning
confidence: 99%